Phytate degradation, intestinal microbiota, microbial metabolites and immune values are changed in growing pigs fed diets with varying calcium–phosphorus concentration and fermentable substrates. Issue 4 (1st April 2019) - Heyer, Charlotte Maria Elisabeth; Schmucker, Sonja; Burbach, Katharina; Weiss, Eva; Eklund, Meike; Aumiller, Tobias; Capezzone, Filippo; Steuber, Julia; Rodehutscord, Markus; Hoelzle, Ludwig Eduard; Seifert, Jana; Mosenthin, Rainer; et al.
Abstract: The present study assessed effects of diets containing varying calcium–phosphorus (CaP) concentration and fermentable substrates on digestibility of diets, intestinal microbiota and immune system using 32 crossbred pigs (initial BW 54.7 kg). In a 2 × 2 factorial arrangement, pigs were fed either a corn–soybean meal (CSB) or corn–field pea (CFP) diet with either low [‐] (4.4 g Ca/kg; 4.2 g total P/kg) or high [+] (8.3 g Ca/kg; 7.5 g total P/kg; supplemented with monocalcium phosphate) CaP content for a period of 9 weeks. In week 8, blood samples were taken, and at the end of the trial, all pigs were euthanized to collect digesta and mesenteric lymphoid tissue. Apparent total tract digestibility (ATTD) of P was greater ( p  < 0.05) for pigs fed the CaP+ and CFP diets than CaP‐ and CSB diets. The myo ‐inositol 1, 2, 3, 4, 5, 6‐hexakis (dihydrogen phosphate) (InsP6 ) concentration in jejunal digesta was higher ( p  < 0.05) for CaP+ than in CaP‐ fed pigs. In addition, caecal and faecal InsP5 isomer concentration were greater ( p  < 0.05) for CSB than CFP diets. In the caecum, gene copy numbers of saccharolytic bacteria, such as Eubacterium rectale and Roseburia spp., as well as SCFA concentration were higher ( p  < 0.05) for CaP+ than CaP‐ diets. In particular, innate immune cell numbers, such as natural killer cells, dendritic cells, monocytes and neutrophils, were greater ( p  < 0.05) for CaP+ than CaP‐ fed pigs. Diets high in CaP resulted in higher abundance of potential beneficial bacteria and might promote the first line of defence enhancing the activation of the cellular adaptive immune response, thereby possibly decreasing the risk for intestinal disturbances. These results strongly suggest that both, CaP supply and dietary ingredients differing in fermentability, may beneficially affect gut health through increase in SCFA‐producing bacteria and/or bacteria with anti‐inflammatory properties.